2012
DOI: 10.1086/666613
|View full text |Cite
|
Sign up to set email alerts
|

Anthropogenic Harvesting Pressure and Changes in Life History: Insights from a Rocky Intertidal Limpet

Abstract: The importance of large breeding individuals for maintaining the health of marine fish and invertebrate populations has long been recognized. Unfortunately, decades of human harvesting that preferentially remove larger individuals have led to drastic reductions in body sizes of many of these species. Such size-selective harvesting is particularly worrisome for sequentially hermaphroditic species where the larger size classes are composed primarily of one sex. Whether these species can maintain stable sex ratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 48 publications
(74 reference statements)
2
34
0
Order By: Relevance
“…; Hawkins et al. ), Chile (Oliva and Castilla ; Duran and Castilla ), Mexico, and California (Pombo and Escofet ; Fenberg and Roy , ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…; Hawkins et al. ), Chile (Oliva and Castilla ; Duran and Castilla ), Mexico, and California (Pombo and Escofet ; Fenberg and Roy , ).…”
Section: Introductionmentioning
confidence: 99%
“…Although it changes sex from male to female as it grows in size, in common with other exploited species (e.g., some Patella spp., C. oculus, and L. gigantea ), few studies have addressed experimentally the potential implications of human exploitation on demographic sex ratios (but see Rivera‐Ingraham et al. ; Fenberg and Roy ; for descriptive data on protected and exploited populations). This reflects the difficulty of following sex change in an individual through its life (but see Wright and Lindberg ; Le Quesne and Hawkins ).…”
Section: Introductionmentioning
confidence: 99%
“…Kido & Murray, 2003;Branch & Odendaal, 2003;Martins et al, 2011;López et al, 2012). Highly vulnerable species are more likely to benefit from the establishment of protected areas, as demonstrated by case studies on large limpets that are often present within MPAs and other protected areas (Fenberg & Roy, 2012;Espinosa et al, 2014;García-Gómez et al, 2015). The Sinis MPA was established more than fifteen years ago in an area where human pressure on marine resources was intense (Casola et al, 2014;Pieraccini et al, 2017) and where the gathering of intertidal organisms was frequently performed as a recreational activity by local communities (Coppa et al, 2012).…”
Section: The Role Of the Mpa And Of Physical Accessibilitymentioning
confidence: 99%
“…Several case studies have demonstrated declines in limpet populations as a consequence of human harvesting (Ferraz et al, 2001;Weber & Hawkins, 2002;Navarro et al, 2005;Sagarin et al, 2007;Fenberg & Roy, 2012), especially in populated areas. Harvesting intensity is often limited by the physical features of an area, which can reduce the number of collectors visiting a site (Garcia & Smith, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the natural and anthropogenic factors complex geo-chemical element associations are forming in gastropod shells and muscles. As a result it may change organism functions, and exhaust adaptive resources [5]- [8].…”
Section: Introductionmentioning
confidence: 99%